MAmIoTie: An Affective and Sensorized Toy to Support Emotion Perception - Raúl García-Hidalgo; Esperanza Johnson; Ramón Hervás; Iván González; Tania Mondéjar; José Bravo (Proceedings, 2018)
Affective Computing aims at developing systems to recognize, process and interpret emotions. This paper presents a sensorized toy with affective functionalities through cognitive services based on IBM Watson technology. The purpose of this research is to improve the quality of life through the assistance oftherapies with children and preadolescents to support emotion perception. This is focused from three points of view: (a) self-perception, (b) empathy and, (c) social-emotional skills. MAmIoTie was evaluated with 10 healthy preadolescent subjects to assess how effectively it analyzes users’ emotional perception. The results were generally positive in terms of analysis, though there were aspects that behaved in a way we did not expect.